2020
DOI: 10.1111/ctr.14157
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation as a bridge vs. non‐bridging for lung transplantation: A systematic review and meta‐analysis

Abstract: Whether extracorporeal membrane oxygenation (ECMO) as a bridge to lung transplantation (BTT) can achieve a similar survival to non‐BTT remains controversial. We conducted this meta‐analysis to compare the outcomes between ECMO BTT and non‐BTT to facilitate better clinical decision‐making. Seven databases were searched for eligible studies comparing ECMO BTT and non‐BTT. The primary endpoints included survival, intraoperative indicators, postoperative hospitalization indicators, and postoperative complications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Overall, mortality rates in our review are consistent with published experience on ECMO use as bridge to lung transplantation (74), but lower than reported in case series and major randomized controlled trials (RCTs) on ECMO for ARDS (75). It is possible that careful selection of ARDS patients for awake ECMO may have resulted in enrollment of low-risk patients only.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, mortality rates in our review are consistent with published experience on ECMO use as bridge to lung transplantation (74), but lower than reported in case series and major randomized controlled trials (RCTs) on ECMO for ARDS (75). It is possible that careful selection of ARDS patients for awake ECMO may have resulted in enrollment of low-risk patients only.…”
Section: Discussionsupporting
confidence: 88%
“…The observed mortality rate in this study aligns with findings from two prior systematic reviews ( 30 , 31 ). An earlier meta-analysis revealed that patients receiving long-term ECMO-supported lung transplantation as bridging therapy had a worse prognosis compared to those not receiving ECMO.…”
Section: Discussionsupporting
confidence: 91%
“…However, in a recent meta-analysis comparing non-bridged and ECMO-bridged LTx patients using 19 studies, non-bridged LTx patients showed better 1-year to 5-year survival rates and fewer complications compared with the ECMO-bridged LTx patients [ 20 ]. In summary, whether ECMO as a bridge to LT can achieve survival rates similar to those of non-bridged LTx patients remains controversial.…”
Section: Outcome Of Ecmo As a Bridge To Ltxmentioning
confidence: 99%
“…The results of multivariate analysis in previous meta-analysis study showed that awake status (relative risk [RR], 2.7; 95% confidence interval [CI], 1.29–5.65), extubated on ECMO (RR, 5.39; 95% CI, 0.79–36), and ambulation (RR, 7.58; 95% CI, 2.16–26.62) were predictors of successful bridge to LTx [ 20 ]. Consistent with these factors, several studies have reported positive results associated with the use of ECMO as a bridge to LTx, such as awakening, minimal sedation, spontaneous breathing, and physical activity during ECMO [ 11 , 16 , 21 ].…”
Section: Outcome Of Ecmo As a Bridge To Ltxmentioning
confidence: 99%